P049 Pharmacist 5Ps- positive PRAISe produces pleasing prescribing. Issue 7 (19th June 2019) - Cope, Aimee; Plunkett, Adrian; Jones, Alison; Chan, Alice; Price, Katie; Isaac, Rhian
Abstract : Aim: Learning from Excellence (LfE), a positive reporting initiative, has two main objectives: to capture and learn from episodes of excellent practice and boost morale through positive feedback. The PRAISe project, 2 tests the hypothesis that positive reporting and appreciative inquiry (AI) can be used as interventions to facilitate behavioural change and improvement in antimicrobial stewardship. Methods: LfE was applied as a quality improvement (QI) intervention for antimicrobial use on PICU over a 12 month period: baseline (3 months), intervention (6 months) and post intervention (3 months) phases. 31 PICU charts were screened weekly by PICU research nurses, this included any documentation added by a pharmacist to improve antimicrobial stewardship. Positive reports (IR2) were generated for gold standard prescriptions and excellence in antimicrobial stewardship, followed up by AI. QI suggestions derived from AIs were applied to the antimicrobial stewardship programme of the unit e.g. RAG rating antibiotics to the prescription charts. PICU pharmacists recorded interventions relating to antimicrobials during the data collection period. Pharmacist interventions were split into proactive or reactive: proactive involving advance confirmation that prescriptions were individualised to best therapy for patients and reactive if a prescription was incorrectly written or no clarification was sought from the pharmacist during ward round. Mini-AI interviews were conducted with the pharmacists at the end of the QI project to assess their opinions on changes to the antimicrobial stewardship programme. Results: The chart reviews by nursing staff highlighted 98 pharmacist interventions at baseline, 275 during the intervention phase and 80 post intervention. The pharmacists recorded an extra 138, 340 and 135 baseline, during and post intervention. Proactive intervening increased during each phase 68 (49.2%), 183 (53.8%) and 84 (62.2%), respectively. Thirty eight out of the 613 (6.2%) extra interventions were not accepted, with 25 (65.7%) of these being reactive. Gold standard prescribing improved during the intervention stage and was sustained in the post intervention phase. QI interventions brought out from the AIs involving pharmacists included RAG rating antibiotics according to priority to de- escalate to a narrower spectrum and presence at the daily microbiology round to document and communicate decisions to the wider team. AIs held with the pharmacists post project included the following themes: improved antimicrobial knowledge and understanding for directed therapy, greater communication 'as now part of the PICU microbiology team', 'increased confidence to challenge antimicrobial decisions'. The pharmacists perceive there continues to be an increase in antimicrobial discussions on the daily PICU ward round. Conclusion: Positive re-enforcement can improve a prescriber's antimicrobial prescribing and documentation and encourage them to proactively seek pharmacy input to ensure best directed therapy for antimicrobials. This contributes to the overall quality of antimicrobial stewardship and patient care on the unit. References: Kelly N et al Learning from excellence in healthcare: a new approach to incident reporting . http://adc.bmj.com/content/101/9/7882 Plunkett A, et al. Positive Reporting and Appreciative Inquiry in Sepsis (PRAISe) . https://www.health.org.uk/improvement-projects/positive-reporting-and-appreciative-inquiry-in-sepsis-praise (Accessed 13 May 2019)